PaletteStream: A Promotional, and Community Web-Based Platform for Visual Artists with Gamification Implementation - Yunia Ikawati; Rosyid Ferdiansyah; Mohammad Robihul Mufid; Darmawan Aditama; Saniyatul Mawaddah (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2025)
In the digital era, social media has become a primary medium for visual artists to promote their work and engage with audiences. However, mainstream platforms such as Instagram and Facebook often fall short of addressing the specific needs of artists due to algorithms that are not tailored to the art domain. While specialized platforms like DeviantArt and ArtStation exist, most have yet to implement effective gamification features that could enhance user engagement and motivation. To address these challenges, PaletteStream is developed as a dedicated web-based platform for visual artists, focusing on collaboration, promotion, and community building. By integrating gamification elements using MVC Architecture, PaletteStream aims to facilitate artistic collaboration, improve the efficiency of art promotion, and foster an active and supportive artistic community. This project also contributes to technological innovation in the arts and advances in application development centered on user experience. The results reveal that the PaletteStream Platform for gamification systems properly awards points and badges based on established rules and provides considerable performance gains with an average API response time of less than 3 seconds.